2019
DOI: 10.3390/ijms20122916
|View full text |Cite
|
Sign up to set email alerts
|

Initial Harm Reduction by N-Acetylcysteine Alleviates Cartilage Degeneration after Blunt Single-Impact Cartilage Trauma in Vivo

Abstract: Joint injuries are highly associated with the development of post-traumatic osteoarthritis. Previous studies revealed cell- and matrix-protective effects of N-acetylcysteine (NAC) after ex vivo cartilage trauma, while chondroanabolic stimulation with bone morphogenetic protein 7 (BMP7) enhanced type II collagen (COL2) expression. Here, as a next step, we investigated the combined and individual efficacy of intra-articular antioxidative and chondroanabolic treatment in a rabbit in vivo cartilage trauma model. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(38 reference statements)
4
7
0
Order By: Relevance
“…In general, chondrocyte death leads to hypocellularity, which not only comes along with reduced capacities for ECM production, but also promotes cell cluster formation, which is commonly regarded as a possible compensatory response of the cells. In our rabbit in vivo cartilage trauma model, severe hypocellularity was observed 12 weeks after traumatic impact of about 1.0 J, though occasional proliferation was found as indicated by cell cluster formation [124,125]. Comparable findings could be demonstrated in our human ex vivo cartilage trauma model after an impact of 0.59 J; trauma-related cell loss at day 7 after impact was sort of compensated by cluster formation as shown at day 14 [66].…”
Section: Chondrocyte Death and Cluster Formationsupporting
confidence: 67%
See 4 more Smart Citations
“…In general, chondrocyte death leads to hypocellularity, which not only comes along with reduced capacities for ECM production, but also promotes cell cluster formation, which is commonly regarded as a possible compensatory response of the cells. In our rabbit in vivo cartilage trauma model, severe hypocellularity was observed 12 weeks after traumatic impact of about 1.0 J, though occasional proliferation was found as indicated by cell cluster formation [124,125]. Comparable findings could be demonstrated in our human ex vivo cartilage trauma model after an impact of 0.59 J; trauma-related cell loss at day 7 after impact was sort of compensated by cluster formation as shown at day 14 [66].…”
Section: Chondrocyte Death and Cluster Formationsupporting
confidence: 67%
“…The following in vivo study confirmed, that combination of BMP7 and NAC did not result in more beneficial effects as compared to the monotherapeutic approaches [124]. Although we expected that the efficacy of the growth factors would be enhanced with respect to the NAC-mediated clearance of ROS and NO, we rather observed mutual interference between the therapeutic substances to some extent [66,124]. These experiences led to the conclusion that a sequential application-that first aims at initial harm reduction by addressing the upstream events and respective effector molecules, thus paving the path for a subsequent chondroanabolic stimulation-might provide a more promising outcome [22,66].…”
Section: Pharmacologic Modulation Of Chondrocyte's Behavior and Fatesupporting
confidence: 60%
See 3 more Smart Citations